PENGARUH SELF ESTEEM TERHADAP PRESTASI BELAJAR SISWA KELAS IV SDN KARANG TENGAH 7 - Amelia Riski Padilah Nasution; Bahar, Herwina; Herli Sundi, Venni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Teacher dominance in teacher-centered learning model Passive learning, students easily chat with their friends next to them, noisy when the teacher is explaining the material or busy with objects around them, so that when the teacher asks questions to students, not all students understand the material presented. Students who do not understand the material given by the teacher can result in students being left behind in doing assignments, students who do not understand what is being learned make students ask their friends, foster a sense of insecurity about themselves. This study aims to investigate the effect of self-esteem on the learning achievement of fourth grade students at SDN Karang Tengah 7 using the survey method. Data analysis using a simple linear regression test with a significance level of 0.5 (5%) F test regression obtained Fcount> Ftable (0.108> 2.30) The results of the F test indicate that there is no significant effect between self-esteem and fourth grade students' learning achievement. Simple linear regression shows a positive relationship between self-esteem and learning achievement (Y = 66.424 + 0.282X). In conclusion, self-esteem does not have a significant influence, but its effect is limited, with other factors also influencing student learning achievement.